2007
DOI: 10.4081/gh.2007.251
|View full text |Cite
|
Sign up to set email alerts
|

Stratifying land use/land cover for spatial analysis of disease ecology and risk: an example using object-based classification techniques

Abstract: Abstract. Landscape epidemiology has made significant strides recently, driven in part by increasing availability of land cover data derived from remotely-sensed imagery. Using an example from a study of land cover effects on hantavirus dynamics at an Atlantic Forest site in eastern Paraguay, we demonstrate how automated classification methods can be used to stratify remotely-sensed land cover for studies of infectious disease dynamics. For this application, it was necessary to develop a scheme that could yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…[3][4][5][6][7][8] Environmental changes in habitat could lead to an increase in virus transmission risk from infected rodents to humans. [4][5][6][7][8][9] Studies on HPS indicated that the emergence of hantavirus was associated with weather and climatic events like El Niño Southern Oscillation. 3,10,11 The prevalence of HFRS in China was determined by various environmental factors such as elevation, precipitation, temperature, vegetation, and soil types.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Environmental changes in habitat could lead to an increase in virus transmission risk from infected rodents to humans. [4][5][6][7][8][9] Studies on HPS indicated that the emergence of hantavirus was associated with weather and climatic events like El Niño Southern Oscillation. 3,10,11 The prevalence of HFRS in China was determined by various environmental factors such as elevation, precipitation, temperature, vegetation, and soil types.…”
Section: Introductionmentioning
confidence: 99%
“…Promising results had already been published on Rift Valley fever in Kenya by Linthicum et al (1990) and the relationship of trypanosomiasis and its tsetse fly vectors to satellite imagery by Rodgers and Randolph (1991). Under the umbrella concept of "landscape epidemiology" initiated by Pavlovsky (1966), these early efforts were soon joined by other researchers (Galuzo, 1975;Kitron, 1998;Koch et al, 2007;Estrada-Peña, 2009;Anaruma Filho et al, 2010;Delgado-Petrocelli et al, 2011).…”
Section: Geospatial Technologies and Neglected Tropical Diseases (Ntds)mentioning
confidence: 99%
“…Landscapes are complex systems, displaying a dynamic interplay between structure (the spatial relationship among distinct elements or structural components of a system) and function (the productivity, nutrient cycling, animal movement and population dynamics of a system) [35,96,97]. In this landscape epidemiological view, disease occurrence can arise not just from the presence of a habitat, but from the underlying variations in these landscapes [54,98]. Land use/land cover maps have been used to examine the interplay between pattern and process across a range of environmental sciences.…”
Section: Review Of the Use Of Discrete Products In Public Health Resementioning
confidence: 99%
“…Commercially available software commonly used in geographic OBIA applications, such as eCognition (previously known as Definiens' eCognition) [22,30,41,50,51] were influenced in their early development by such analysis of images from cell-based assays, whole tissue slides and full body scans [52,53], and indeed the two arenas, medical OBIA and geographic or environmental OBIA, continue to develop side-by-side with few interdisciplinary publication outlets. While it is the classification accuracy benefits to OBIA that are most often cited in the public health remote sensing literature [54,55], it is the ability of OBIA to capture fundamental spatial content across scales, and their interactions, that can be critical to understanding a system. This type of spatial content could be more frequently used in public health applications to understand complex systems and their interrelations.…”
Section: Introductionmentioning
confidence: 99%